South from Hell-fer-Sartin : Kentucky mountain folk tales - Roberts, Leonard W (University of Kentucky Press, 1988)
South from Hell-fer-Sartin, a short creek flowing into the Middle Fork of the Kentucky River, lies one of the of the most isolated regions in Kentucky. There, on the north slope of the Pine Mountain range in Leslie and Perry counties -- probably the last stronghold of white, English-language folk tales in North America -- Leonard W. Roberts recorded this rich collection more than three decades ago. To a people who, at that time, watched dancing hearth fires more often than television, the adventures of Jack in the land of witches and giants, monsters and beautiful princesses, provided first-cla.